VD_FINDINFO HC / 2024 / 606 vom 30. Oktober 2024 - VD Tribunal cantonal (2024)
MAXIME INQUISITOIRE, PRINCIPE DE LA BONNE FOI, NOVA, REVENU HYPOTHÉTIQUE, OBLIGATION D'ENTRETIEN | 296 al. 1 CPC (CH), 317 al. 1 CPC (CH), 52 CPC (CH)